Towards the vulnerability assessment of low-code RC frame buildings at precarious slopes subjected to rainfall induced landslide hazard. (December 2021) - Fotopoulou, Stavroula D.; Pitilakis, Kyriazis D.
Abstract: The presence of capillary pressure in unsaturated soils may, under certain circumstances, significantly affect the stability of a slope and the safety of a structure standing in the vicinity of its crest. More specifically, the change in saturation induced by a rainfall event may directly influence the value of apparent soil cohesion potentially resulting in excessive permanent slope displacements and subsequent structural damages for the structure standing on it. Under these considerations, this study aims at the vulnerability assessment of typical reinforced concrete (RC) buildings on precarious slopes subjected to rainfall induced landslide hazard. The proposed methodology is based on a two-step numerical analysis procedure. First, the permanent absolute and differential ground displacement time histories at the assumed building location within the landslide zone are evaluated performing coupled mechanical-flow analysis of a generic initially unsaturated natural slope configuration considering the employment of different rainfall events of increased intensity at the surface of the slope model. Different soil properties of the surface layer are considered to represent silty and soft clayey soil material. Appropriate analytical relationships between the rainfall intensity and its duration and the computed permanent displacements are extracted. Then, a series of nonlinear static time history analyses are performed for reference low and mid-rise, low-code RC bare and infilled frame buildings located next to the slope's crest to assess their fragility. The buildings' response assessed using appropriate engineering demand parameters (EDPs) to account for both the global flexural and local shear demand are statistically correlated with predefined damage limit states to construct the fragility functions. To facilitate the applicability of the proposed methodology within a quantitative landslide risk assessment framework, vulnerability curves are finally developed to quantify the expected direct losses in normalised cost terms.